1999
DOI: 10.1007/0-306-46937-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Rheological Relation of Materials by Taking into Account the Rate-dependent Evolution of Internal Defects at High Strain Rates

Abstract: It was experimentally observed that a rheological process of material is usually accompanied with an evolution of internal defects or micro-damage. Based on the micro-observation of the twinning evolution for Zircaloy-4, the adiabatic shear banding evolution for titanium alloy TB2 and the micro-cracks evolution for cast magnesium alloy ZM5-T4, thermoplastics PMMA and cement mortar, a rate-dependent defect/damage evolution law is suggested on the basis of thermo-activated mechanism. Correspondingly, a damage-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Such transverse inertia noises may be negligible in the experiments for most high‐strength alloys but become un‐negligible for low wave‐impedance materials such as porous materials. One possible way to overcome this difficulty is to use the pulse‐shaping technique [3], although the test strain rate may decrease correspondingly. The evolution of internal damage, which will display more significant influence on the apparent constitutive response of materials with increase of both strain and strain rates [4]. In fact, it has been observed that, if the strain is large enough and the strain rate is high enough, the deformation process of any material is usually accompanied with an evolution of internal damage, the accumulation of which will lead to the final failure of polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such transverse inertia noises may be negligible in the experiments for most high‐strength alloys but become un‐negligible for low wave‐impedance materials such as porous materials. One possible way to overcome this difficulty is to use the pulse‐shaping technique [3], although the test strain rate may decrease correspondingly. The evolution of internal damage, which will display more significant influence on the apparent constitutive response of materials with increase of both strain and strain rates [4]. In fact, it has been observed that, if the strain is large enough and the strain rate is high enough, the deformation process of any material is usually accompanied with an evolution of internal damage, the accumulation of which will lead to the final failure of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of internal damage, which will display more significant influence on the apparent constitutive response of materials with increase of both strain and strain rates [4]. In fact, it has been observed that, if the strain is large enough and the strain rate is high enough, the deformation process of any material is usually accompanied with an evolution of internal damage, the accumulation of which will lead to the final failure of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…For frozen soil, referring to some relevant research on metals and concrete, we shall establish a damage evolution equation by using the thermal activation theory to explain the damage evolution law of frozen soil (Arsenault, 1978). Wang et al (1999) conducted several dynamic tests and showed that the damage evolution process is a rate process that is similar to the rate process of viscoplatic deformation. Thus, from equation 3, the following function can be determined by analogy (Wang et al, 1999)…”
Section: Damage Evolutionmentioning
confidence: 99%
“…Wang et al (1999) conducted several dynamic tests and showed that the damage evolution process is a rate process that is similar to the rate process of viscoplatic deformation. Thus, from equation 3, the following function can be determined by analogy (Wang et al, 1999)…”
Section: Damage Evolutionmentioning
confidence: 99%
See 1 more Smart Citation